A coarse grained molecular dynamics study on the structure and stability of small-sized liposomes. Issue 2 (22nd January 2016) - Tamai, Hideaki; Okutsu, Naoko; Tokuyama, Yuki; Shimizu, Eisuke; Miyagi, Satoshi; Shulga, Sergiy; Danilov, Victor I.; Kurita, Noriyuki
Abstract : The dependence of geometric structure and thermal stability of liposomes on their component phospholipid molecules and distribution of molecules in the inner and the outer layers of the liposome is investigated by conducting molecular simulations in explicit water for the eight types of liposomes constructed from different phospholipids. Using molecular mechanics structure-relaxation based on the coarse grained (CG) model, stable structures of the solvated liposomes are obtained. In addition, the molecular dynamics (MD) simulations based on the CG model are carried out at 310 and 360 K for elucidating the change in structure of the solvated liposomes. The MD simulations reveal that liposomes having the same number of lipids (SNL) in both the inner and the outer layers keep their spherical structures even at 360 K. In particular, the SNLs composed of palmitoyloleoyl-phosphatidyl-ethanolamine1 or dimyristoylglycero-phosphatidyl-choline lipid exhibit a compact spherical shape. In contrast, liposomes having the same density of lipids in the inner and the outer layers cannot keep their spherical shapes at 360 K. The obtained results contribute toward developing novel liposomes with enhanced thermal stability.